Application of matrix-assisted laser desorption/ionization mass spectrometry imaging in combination with LC–MS in pharmacokinetic study of metformin. (January 2018) - Strnad, Štěpán; Vrkoslav, Vladimír; Klimšová, Zuzana; Zemenová, Jana; Cvačka, Josef; Maletínská, Lenka; Sýkora, David
Aim: To demonstrate and discuss the pros and cons of various conventional and innovative analytical approaches.Methodology & results: Matrix-assisted laser desorption/ionization mass spectrometry imaging (MSI) of tissue sections as well as the extraction of tissue homogenates, blood plasma and dried blood spots coupled with LC–MS were employed to monitor the pharmacokinetics of metformin in mice. The time profile of metformin measured by matrix-assisted laser desorption/ionization MSI correlated well with the results found by LC–MS. Repeatability of the preparation of tissue sections for MSI was very good.Conclusion: MSI provided valuable information on the spatial distribution and relative concentration of the analyte within tissue sections. The analysis of the extracts of tissue homogenates, blood plasma and blood spots provided quantitative data on metformin. The dried blood spot approach is a progressive method of sampling, especially in studies where the amount of available blood is limited. Graphical abstract: